Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jgc4.1433
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal genetic counselors' perceptions of the impact of abortion legislation on counseling and access in the United States

Abstract: Genetic counselors have an important role in offering and appropriate coordinating abortion services for patients identified with a fetal abnormality. Few studies have been conducted to determine the effects of legislation on genetic counselors and patients. This study aimed to further our understanding of genetic counselors' perception of the impact of abortion regulations on their practice, the perceived financial and emotional impact on their patients and their ability to access abortion.A 22-question surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This study also concluded that, according to GCs, these restrictions create significant financial and emotional burdens for their patients, amplifying the impact of reduced access. Collectively, these studies suggest existing abortion restrictions negatively impact the duration of time available for a patient's reproductive decision-making following results from prenatal screening and/or diagnosis and that this time pressure affects the practice of prenatal genetic counseling (Jayaraman et al, 2021).…”
Section: What This Paper Adds To This Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also concluded that, according to GCs, these restrictions create significant financial and emotional burdens for their patients, amplifying the impact of reduced access. Collectively, these studies suggest existing abortion restrictions negatively impact the duration of time available for a patient's reproductive decision-making following results from prenatal screening and/or diagnosis and that this time pressure affects the practice of prenatal genetic counseling (Jayaraman et al, 2021).…”
Section: What This Paper Adds To This Topicmentioning
confidence: 99%
“…As a result, some GCs described becoming more involved with reproductive advocacy initiatives in their states (Koenig et al, 2019). Most recently, Jayaraman et al (2021) examined the issues identified by Koenig et al (2019) in a larger cohort, concluding prenatal GCs and their patients are impacted by restrictive abortion legislation—particularly legislation centered on gestational age limits. This study also concluded that, according to GCs, these restrictions create significant financial and emotional burdens for their patients, amplifying the impact of reduced access.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interviews with 16 reproductive genetic counselors from multiple states reveal their concern for their patients’ ability to access abortion services, as well as fear that the current legislation will perpetuate stigma surrounding abortion and lead to future abortion restrictions (Koenig et al., 2019). Nationwide, genetic counselors report the perception that their patients experience financial and emotional burdens, and a detrimental impact on the genetic counselors themselves in regard to their counseling and coordination of abortion services (Jayaraman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%